Interactive Visual-Art-centered Learning Activities in Developing Thinking Skills and Creativity - Stavridi, Sylvia (Research Highlights in Language, Literature and Education Vol. 4, 2023)
Interactive arts-based learning methods is a modernized approach to nurture creativity in education. Visual-arts centered learning/teaching experience provides primary school students the opportunity to interact in a constructive instructional setting. In this sense, modernizing the process of learning by “teaching through visual-arts,” in which primary school students are meaningfully stimulated to visualize the creative-links between specific visual-art forms and the anchor concepts of core content areas in education, such as science/math and technology from a broad perspective. The chapter focuses on the interrelation between interactivity in contemporary abstract visual-art and creative-thinking. Supported by interactive-technology, visual-arts learning activities generate investigative paths to imaginative/creative-thinking. This chapter outlines the importance of the use of specific art-forms as a connective pathway of integrating arts into the teaching of traditional academic abstract content exist for primary school students to further their interaction and artistic development in an increasingly smart-context. In the remainder of this chapter, the author underexplores the fact that integrated digital-aesthetic learning instruments have fundamentally renewed the focus from not only fulfilling the existing education system, but also pick up higher level of innovative/interactive/effective forward-focused teaching-learning settings. A study was conducted to compare, evaluate, and validate the effectiveness of visual-arts-based pedagogy digital-technology blended in competing views of different art-tech software/web-based applications that support the benefits of innovative active-learning. The author then concludes with an emphasis on the efficient use of aesthetic digital-technologies through primary education as a tool to create stimulated activities to improve students' learning in a creative-process.